Analgesic efficacy of hydromorphone in American alligators (Alligator mississippiensis) - Henke, Scott E.; Wester, David B.; Eversole, Cord B.; Huerta, Javier O.; Hilton, Clayton D.; Sladky, Kurt K. (Frontiers in Veterinary Science, 2025)
BackgroundAmerican alligators (Alligator mississippiensis) are maintained in zoos, aquaria, and farms for educational, research, and production purposes. The standard of veterinary medical care and welfare for captive reptiles requires managing pain and discomfort under conditions deemed painful in mammals. While analgesic efficacy and pharmacokinetic data for several reptile species are published, data with respect to analgesic efficacy in crocodilians are clearly lacking.ObjectiveThe objective of this study was to determine the analgesic efficacy of hydromorphone in alligators.MethodsFemale American alligators (N = 9; 57 months of age) were exposed to mechanical noxious stimuli at multiple anatomic sites using von Frey filaments ranging in size from 1.65 to 6.65 grams-force, and their behavioral reactions recorded. In order to evaluate analgesic efficacy, hydromorphone (0.5 mg/kg SC) was administered in the axillary region to the same alligators and the mechanical noxious stimuli were repeated and behaviors recorded.ResultsAdministration of hydromorphone contributed to a range from 62 to 92% reduced avoidance reactions to mechanical noxious stimuli for two anatomic sites (i.e., naris and lateral mandible, respectively).ConclusionAlligators did not appear to experience clinically relevant respiratory depression, hypothermia, or other adverse reactions. Therefore, hydromorphone shows promise as an analgesic option to be administered under painful conditions in American alligators.